Pengakuan sebagai Gramatika Intersubjektif Menurut Axel Honneth - Runesi, Sintus T. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
Axel Honneth gives a new direction for Critical Theory from Frankfrut School. He points out that the theoretical foundation of intersubjective relationship is not merely based on the dimensions of human communication as indicated by Habermas, but also on the recognition dimension. He proposes a shift of normative paradigm from the presuppositions of communicative action to the presuppositions of human identity development. This article summarises some of the main ideas of the critical theory of Honneth. It will describe the theoretical direction taken by Honneth that distinguishes it from Habermas, who later helped to find the problem arresting people into various forms of injustice, a pathology that occurs on the level of rationality, which will be described in the second part of this article. The third part will describe Honneth’s thought about recognition as a moral grammar, followed by a review of the three areas of recognition as a practical basis of critical theory. Some conclusions will be drawn concerning the importance of the small dimensions of recognition in contemporary society.